2017
DOI: 10.3389/fnmol.2017.00281
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Activities of Tfap2A and Tfap2B in the Specification of GABAergic Interneurons in the Developing Cerebellum

Abstract: GABAergic inhibitory neurons in the cerebellum are subdivided into Purkinje cells and distinct subtypes of interneurons from the same pool of progenitors, but the determinants of this diversification process are not well defined. To explore the transcriptional regulation of the development of cerebellar inhibitory neurons, we examined the role of Tfap2A and Tfap2B in the specification of GABAergic neuronal subtypes in mice. We show that Tfap2A and Tfap2B are expressed in inhibitory precursors during embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 67 publications
3
38
0
Order By: Relevance
“…We also found correlations between overexpression of miRNAs that target genes essential in neuronal development and remodelling: miR-6824, -335, and -1468 all target SOX4, which participates in Schwann cell myelination [26], whereas miR-6836 targets TFAP2B, which acts in the specification of GABAergic interneurons in developing cerebellum [27]. Interestingly, MYC-miR34a axis, in which miR-34a apoptotic actions are tightly regulated by MYC and this can lead to drug resistance [28], has somehow been confirmed by our study, however the role of miR-4668 (which was also upregulated and targets MYC) in these interactions remains unclear.…”
Section: Discussionmentioning
confidence: 70%
“…We also found correlations between overexpression of miRNAs that target genes essential in neuronal development and remodelling: miR-6824, -335, and -1468 all target SOX4, which participates in Schwann cell myelination [26], whereas miR-6836 targets TFAP2B, which acts in the specification of GABAergic interneurons in developing cerebellum [27]. Interestingly, MYC-miR34a axis, in which miR-34a apoptotic actions are tightly regulated by MYC and this can lead to drug resistance [28], has somehow been confirmed by our study, however the role of miR-4668 (which was also upregulated and targets MYC) in these interactions remains unclear.…”
Section: Discussionmentioning
confidence: 70%
“…To define the molecular profile of IntA Ucn3 neurons, we performed immunohistochemistry on YFP ON neurons using glutamatergic markers SMI32, also known as neurofilament H which has previously been shown to mark cell bodies and dendrites of large glutamaergic cells in the DCN and TBR1 (T-box receptor 1, a transcription factor which marks glutamatergic cells in the DCN ( Figure 6C, E-H) (Chung et al, 2009;Fink et al, 2006). We also stained neurons with gabaergic markers of the cell body GAD67, and nucleus TFAP2A (transcription factor AP2A) ( Figure 6I-L) (Zainolabidin et al, 2017). We found that…”
Section: Defining the Electrophysiology And Molecular Properties Of Imentioning
confidence: 79%
“…Cell reports 22, 2322-2333. and third author on the second paper: Zainolabidin, N., Kamath, S.P., Thanawalla, A.R., and Chen, A.I. (2017).…”
Section: Authorship Attribution Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all neurons that exhibited glutamatergic electrophysiological properties in the IntA nucleus were recombined in the Ucn3::Cre; Rosa::ChR2-eYFP mice ( Figure 13B-H). To determine the molecular profiles of the IntA Ucn3 neurons and whether these neurons are a subset of the glutamatergic neurons in the DCN, the expression of vGluT2 and GABAergic molecular markers (Gad67, Calretinin or Tfap2A) in eYFP ON neurons was assessed (Zainolabidin et al, 2017;Chung et al, 2009;Leto et al, 2006). SMI32 was used to identify both excitatory and inhibitory subtypes (Leto et al, 2006).…”
Section: Inta Ucn3 Neurons Are a Subpopulation Of Glutamatergic Neuromentioning
confidence: 99%